Flutter performance of shape memory alloy-embedded 3D woven flexible composite plate under subsonic flow - M. Baitab, Danish; Majid, Dayang L.; Abdullah, Ermira J.; A. Hamid, Mohd Faisal; Jang, Leong S.; Halder, Ishan Mitra (Sage Publications, 2022)
Recently, 3D composites have gained prominence over 2D composites due to their remarkable through-the-thickness reinforcement that enhanced performances of structures subject to multi-directional stress conditions. However, it is at the expense of reduced in-plane properties. 3D composites also increased damage tolerance due to their high impact and delamination resistance properties, which are susceptible in 2D composites. In aeronautics, both are major concerns in primary structures such as lifting and control surfaces due to high vibrational loads from the airflow. Advancements in the aeroelasticity of aircraft structures show an increasing trend in using smart materials with composite structures for improved aeroelastic performance. An example is combining shape memory alloys (SMAs) with composites for improving damping, stiffness, and vibrational characteristics by utilizing stress generation and strain accommodation properties of SMAs in response to temperature and load, respectively. Published works are mostly numerical in nature, and experimental research is noticeably lacking as aeroelasticity is multidisciplinary and involves both structural and aerodynamic methodology. In this work, 3D composites with embedded SMA wires (for improved in-plane properties) are evaluated in terms of flutter performance in wind tunnel flutter testing under low airspeed conditions. Three 3D orthogonal interlock configurations with a different interlocking pattern of yarns with SMA wire were considered. These 3D configurations are layer-to-layer (L2L), through-the-thickness (TT), and a modified interlock (MF) structure that provides the strongest grip to SMA wire than L2L and TT. The effect of SMA positioning, at mid and near to trailing and leading edges of the cantilevered composite plate, on the aeroelastic flutter properties is also investigated. Results showed that activating SMA wires embedded in 3D structures have significantly improved post-flutter properties while there is a decrement in flutter speed and flutter frequency due to increased flexibility of deflected plate in the airflow by SMA-induced stresses. Among 3D structures, L2L with SMA near to trailing edge showed significant improvement in post-flutter properties by decreasing 22.2% in twist limit cycle oscillation (LCO) amplitude while L2L with SMA at mid showed a decrement of 9.5% for bending LCO amplitude. Hence, this work showed that embedding SMA is beneficial for mitigating the post-flutter vibrations but at the consequence of reduced flutter speed and frequency of flexible composite plate.